Protein Phosphatase 2A Catalytic Subunit PP2A-1 Enhances Rice Resistance to Sheath Blight Disease - Lin, Qiu Jun; Chu, Jin; Kumar, Vikranth; Yuan, De Peng; Li, Zhi Min; Mei, Qiong; Xuan, Yuan Hu (Frontiers in Genome Editing, 2021)
Rice (Oryza sativa) production is damaged to a great extent by sheath blight disease (ShB). However, the defense mechanism in rice against this disease is largely unknown. Previous transcriptome analysis identified a significantly induced eukaryotic protein phosphatase 2A catalytic subunit 1 (PP2A-1) after the inoculation of Rhizoctonia solani. Five genes encoding PP2A exist in rice genome, and these five genes are ubiquitously expressed in different tissues and stages. Inoculation of R. solani showed that the genome edited pp2a-1 mutants using the CRISPR/Cas9 were more susceptible to ShB than the wild-type control, but other PP2A gene mutants exhibited similar response to ShB compared to wild-type plants. In parallel, PP2A-1 expression level was higher in the activation tagging line, and PP2A-1 overexpression inhibited plant height and promoted the resistance to ShB. PP2A-1-GFP was localized in cytoplasm and nucleus. In addition, R. solani-dependent induction kinetics of pathogen-related genes PBZ1 and PR1b was lower in pp2a-1 mutants but higher in PP2A-1 activation line compared to those in the wild-type. In conclusion, our analysis shows that PP2A-1 is a member of protein phosphatase, which regulates rice resistance to ShB. This result broadens the understanding of the defense mechanism against ShB and provides a potential target for rice breeding for disease resistance.